Realizacja zadań publicznych z zakresu prawa urbanistyczno-budowlanego na przykładzie tzw. inwestycji covidowych - Pilarz, Karina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
The article aims at presenting new legal regulations about building investments during the COVID-19 pandemic. These regulations significantly facilitate and shorten the administrative and building procedures for selected categories of entities, for example by disregarding the obligation to respect the provisions of some normative acts. However, this situation is controversial because of using the rules in a way that is contrary to the purpose of the regulation.
Keywords: public tasks; building regulations; Covid investments; lex COVID; special Covid act